57 Undifferentiated heart sarcoma in young adult: from differential diagnosis to management. (8th December 2021) - Intravaia, Rita Cristina Myriam; Monticelli, Massimiliano; Musca, Francesco; De Chiara, Benedetta; Casadei, Francesca; Pedrotti, Patrizia; Novo, Giuseppina; Giannattasio, Cristina; Moreo, Antonella
Abstract: A 34-year-old patient arrived in Emergency Department (ED) with a history of haemoptysis, fever, and night sweats. Echocardiographic examination revealed a large isoechoic thickening that totally encompassed posterior mitral leaflet and which extended contiguously, both inferiorly with subvalvular apparatus with chordal fusion, and superiorly up to left atrial wall. This alteration caused a moderate mitral stenosis with an estimated average gradient of 10–15 mmHg (with possible overestimation due to temporary state of hyperdynamic circulation secondary to anaemization). There also was an anteriorly directed, eccentric jet of mitral regurgitation (2 +/4 + grade).Differential diagnosis of the aforementioned mitral formation included infectious etiology (endocarditic vegetation), pure phlogistic (inflammatory/rheumatic valvulitis), aseptic vegetation, and thrombosis. Transesophageal echocardiographic evaluation showed the extension of the mass into posterior leaflet, the latter completely englobed from commissure to commissure, and cranially adhered to posterior wall of left atrium with estimated dimensions of 1.9 × 12 mm; inferiorly, contiguity with diffusely thickened subvalvular apparatus and chordal fusion, was appreciated. Resulting stenosis was about 13–14 mmHg. Planimetric mitral valve area was estimated to be about 1 cm with associated mild-moderate regurgitation. Global systolic function was preserved with normal segmental kinesis and without significant anomalies affecting other valves. On cardiac magnetic resonance (CMR) with contrast medium, known sleeve thickening of left atrium (maximum thickness 12 mm in lateral area and 7.5 mm at the level of atrial septum) was extended caudocranially for 2.5 cm in lateral area and for 3.2 cm in the side of the atrial septum and with subocclusion of left inferior pulmonary vein. An esophagogastroduodenoscopy (EGDS) was performed with biopsy examination and subsequent histological typing. It concluded for 'undifferentiated pleomorphic sarcoma' according to the WHO classification of thoracic tumours. In the stomach there was a diffuse infiltration of lamina propria by atypical, pleomorphic, and large cellular elements. Following cancer evaluation, first-line chemotherapy with ifosfamide and doxorubicin was undertaken. Two days later, due to finding of hyperpyrexia, with a feverish peak of up to 39°, infusion of chemotherapy was interrupted and empiric antibiotic therapy (piperacillin tazobactam) was started. Blood and urine cultures were carried out with search for antigens of legionella and pneumococcus, (MRSA), fungi, and respiratory viruses but all of them were negative for active infection. The following day, an episode of acute respiratory failure occurred, so we performed an urgent chest CT with finding of pneumonia with bilateral pleural effusion and linezolid was started. Because of sudden worsening of clinical conditions, patient was transferred to ICCU (Intensive Cardiac Care Unit) with gradual resolution of desaturation. Cardiac ultrasound imaging, from the very first performed in ED, has been fundamental in documenting the presence of a mass in mitral valve. The timeliness in identifying first and then characterizing it certainly had a positive impact on cancer management, especially in such an aggressive neoplasm in a young patient. Furthermore diagnostic process, corroborated by instrumental data provided by ecocardiography, CT, MRI, PET, and scintigraphy, allowed a better staging of the disease and highlighted other organ involvement in order to manage optimal therapeutic approach.